Single-cell sequencing reveals transcriptional dynamics regulated by ERα in mouse ovaries. - Qicai Hu; Yiqian Gui; Congcong Cao; Jun Xie; Huiru Tang (PLoS ONE)
Context Estrogen receptor α (ERα) is a key regulator of reproductive function, particularly in ovarian development and function, yet the specifics of its role at the molecular level remain unclear. Aims The study aims to elucidate the molecular mechanisms of ERα-regulated transcriptional dynamics in ovarian cells using ERα knockout (αERKO) mice created via CRISPR/Cas9. Methods Single-cell RNA sequencing (scRNA-seq) was used to compare transcriptomes from individual ovarian cells in both wild type and αERKO mice. Bioinformatics analyses identified distinct cell populations and their transcriptional profiles post ERα deletion. Key results Distinct oocyte and granulosa cell populations were identified, with ERα deletion disrupting the regulation of genes linked to ovarian infertility, the ovulation cycle, and steroidogenesis. Greb1 expression in granulosa cells was found to be ERα-dependent. Conclusions ERα deletion significantly alters the transcriptional landscape of ovarian cells, affecting genes and pathways central to ovarian function and the ovulation process. Implications The findings provide an in-depth, single-cell view of ERα's role in the reproductive system, offering insights that may lead to novel treatments for ovarian disorders.